2010
DOI: 10.1080/02701960903578329
|View full text |Cite
|
Sign up to set email alerts
|

Intergenerational Service Learning With Elders: Multidisciplinary Activities and Outcomes

Abstract: This article provides an overview of the activities included in a 3-year, multidisciplinary, intergenerational service-learning project conducted as part of a Foundation for Long-Term Care Service Learning: Linking Three Generations grant. Courses from four departments (gerontology, psychology, occupational therapy, and health promotion and physical education) and one interdisciplinary clinical intervention for stroke patients (speech pathology, occupational therapy, and therapeutic recreation) were involved. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 13 publications
4
13
0
Order By: Relevance
“…Service learning promotes learning of new skills and application of those skills in real situations that benefit not only the student, but also the community (Weinreich, 2003). Service learning in gerontology courses leads to students having more positive attitudes toward older adults (Fitzgerald et al, 2006;Krout et al, 2010) and has been shown to improve gerontological competencies (Dauenhauer, Steitz, Aponte, & Fromm Faria, 2010;. Likewise, older adults report developing an increased understanding of the younger generation, valued sharing their life experiences, and enjoying the social contact they had with college students (Underwood & Dorfman, 2006).…”
Section: Interprofessional Education Gerontology and Service Learningmentioning
confidence: 99%
“…Service learning promotes learning of new skills and application of those skills in real situations that benefit not only the student, but also the community (Weinreich, 2003). Service learning in gerontology courses leads to students having more positive attitudes toward older adults (Fitzgerald et al, 2006;Krout et al, 2010) and has been shown to improve gerontological competencies (Dauenhauer, Steitz, Aponte, & Fromm Faria, 2010;. Likewise, older adults report developing an increased understanding of the younger generation, valued sharing their life experiences, and enjoying the social contact they had with college students (Underwood & Dorfman, 2006).…”
Section: Interprofessional Education Gerontology and Service Learningmentioning
confidence: 99%
“…On the one hand, some studies reported positive results in learning outcomes related to the students' personal perceptions, as well as the acquisition of professional skills [27], the knowledge of the consequences of aging among older adults [29], and the perceptions of professional cooperation [30]. On the other hand, outcomes focused on older adults are less studied and mainly address their general perceptions and satisfaction [31][32][33][34]. These results suggest that SL may be an optimal way to promote intergenerational social cohesion and promote older adults' health care [35,36].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we have no doubt that students became more aware of this cycle after participating in the pilot program [12]. Furthermore, the integration of community resources and educational needs specific to clients is a valuable skill for nurses and NPs [13]. In particular, the ability to locate resources and enable clients to access them is crucial in community health and underserved populations.…”
Section: Discussionmentioning
confidence: 97%